Corrosion-resistant high-strength cover plate glass as well as preparation method and application thereof in extreme environment
By using reasonable proportions of SiO2, Al2O3 and other components in the cover glass, the existing cover glass is easily corrosive and insufficient mechanical properties in extreme environments, and the effects of high strength, excellent optical transmittance and good chemical stability are achieved.
Patent Information
- Application Number
- CN202510010766.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing cover glass is prone to corrosion in extreme environments and lacks mechanical properties, which cannot meet the needs of use in cruel extreme environments such as Antarctica.
Corrosion-resistant high-strength cover glass consisting of SiO2, Al2O3, B2O3, K2O, Na2O, CaO, MgO, CeO2, Bi2O3, SnO2, Sb2O3, and Li2O are used to improve the comprehensive performance of the glass by precisely controlling the content of each component.
It achieves high bending strength, excellent optical transmittance, good chemical stability and impact resistance of glass, and is suitable for applications in extreme environments.
Smart Images

Figure CN119822637A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of special glass materials, and relates to corrosion-resistant high-strength cover glass, a preparation method thereof, and applications thereof in extreme environments. Background Art
[0002] In today's era, human activities are spread all over the world. If we want to carry out activities in extreme and complex climate environments, the ability of the materials used in instruments and equipment to resist extreme environmental erosion is one of the difficulties that must be overcome. Antarctica has a very representative harsh climate. The wind speed in coastal areas can reach 45m / s, the air contains a large amount of saline-alkali water vapor, and the ultraviolet radiation is strong. During Antarctic scientific research expeditions, cameras are one of the most commonly used exploration tools. In order to ensure the progress of scientific research and to protect the health of researchers, researchers usually need to place cameras or infrared cameras in the field for a long time to monitor the dynamics of the scientific research area in real time. The camera lens cover is usually made of glass to protect the lens from external environmental erosion. This requires that the cover glass of digital products used in extreme environments such as outdoor environments has high chemical stability, impact resistance, strength, optical transmittance and other properties.
[0003] The optical camera's framing is to project the optical image generated by the lens onto the surface of the sensor and then convert it into an electrical signal, which is then converted into a digital image signal. When the light propagates into the camera to generate an image, some stray light is bound to be generated. Generally, a black absorption layer is prepared on the periphery of the light hole in the glass cover to absorb the stray light, thereby preventing stray light and glare from entering the lens and affecting the exposure. In the first stage of imaging, various factors affecting the imaging are reduced to a minimum, thereby improving the imaging quality. However, the traditional coating to prepare the black absorption layer will have problems such as easy to fall off in extreme environments. At the same time, the stray light absorption rate of the black absorption layer directly affects the imaging quality. Therefore, it is necessary to develop a cover glass that can adapt to harsh and extreme environments such as the Antarctic, so as to ensure the smooth use of optical cameras in such harsh and extreme environments. Summary of the invention
[0004] In order to address the deficiencies in the prior art, the object of the present invention is to provide corrosion-resistant high-strength cover glass, a preparation method thereof, and applications in extreme environments. The cover glass provided by the present invention has excellent performance, not only in terms of spectral transmittance and chemical stability, but also in terms of good anti-halo and anti-crosstalk properties after reduction and chemical strengthening, high mechanical strength, impact resistance and drop resistance, and good processing performance, and can be applied to cover glasses for various extreme environments.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] In a first aspect, a corrosion-resistant high-strength cover glass is composed of the following components in parts by weight:
[0007] SiO2 48.0-60.0 parts by weight, Al2O3 19.0-25.0 parts by weight, B2O3 3.0-7.0 parts by weight, K2O0-2.0 parts by weight, Na2O 13.0-17.0 parts by weight, CaO 0-1.0 parts by weight, MgO 0.5-4.0 parts by weight, CeO2 0.5-2.0 parts by weight, Bi2O3 0-3.0 parts by weight, Sb2O3 0-3.0 parts by weight, SnO2 0.1-2.0 parts by weight, Li2O 0.1-2.0 parts by weight, the total weight of each component is 100 parts by weight;
[0008] Among them, K2O and CaO cannot be 0 at the same time, and Bi2O3 and Sb2O3 cannot be 0 at the same time.
[0009] The corrosion-resistant high-strength cover glass provided by the present invention contains SiO2, Al2O3, B2O3, K2O, Na2O, CaO, MgO, CeO2, Bi2O3, SnO2, Sb2O3, and Li2O at the same time. By precisely controlling the components and contents of SiO2, Al2O3, B2O3, K2O, Na2O, CaO, MgO, CeO2, Bi2O3, SnO2, Sb2O3, and Li2O, excellent comprehensive performance is achieved, including strength, chemical stability, optical transmittance, and reduced black layer stray light absorption rate. The integrated effect of SiO2, CaO, B2O3, and MgO jointly improves the thermal stability and chemical stability of the glass. As the main component, SiO2 provides the basis of the structure; the synergistic effect of CaO, B2O3, and CaO adjusts the thermal expansion coefficient and enhances the chemical stability. The addition of MgO further improves the corrosion resistance of the glass in complex environments and extends its service life. The introduction of Al2O3, MgO, B2O3, CeO2 and Li2O improves the optical quality and enhances the optical transmittance of glass materials. In addition, by adjusting the content of Al2O3, Li2O, MgO and CaO, the tendency of glass crystallization is effectively reduced, and the transmittance of glass after molding is further improved. The combined action of Na2O, SnO2, Sb2O3, CeO2 and B2O3 reduces the difficulty of glass clarification and reduces defects such as bubbles during glass melting. In addition, the synergistic effect of two or three of the three oxidizing compounds Bi2O3, SnO2 and Sb2O3 improves the absorption rate of stray light after glass reduction and blackening.
[0010] By controlling the contents of CaO, K2O, Na2O, CeO2 and B2O3, the viscosity of molten glass can be reduced and the difficulty of glass molding can be reduced; by controlling the contents of SiO2, Al2O3, Li2O, Na2O and K2O, the tendency of glass crystallization can be reduced and the permeability of glass after molding can be improved. By controlling the contents of SiO2, Al2O3, CaO and MgO, the chemical stability of glass can be improved, the corrosion resistance of glass in extreme environments can be improved, and the service life of glass can be extended. By controlling the contents of K2O, Na2O, CeO2, SnO2 and Sb2O3, the difficulty of glass clarification can be reduced and defects such as bubbles in the glass melting process can be reduced.
[0011] In a second aspect, a method for preparing the corrosion-resistant high-strength cover glass according to the first aspect of the present invention comprises the following steps:
[0012] Mixing the components of the glass material uniformly in proportion to obtain a mixture;
[0013] The mixture is melted at 1480-1580°C, stirred, clarified, and molded at 1350-1400°C.
[0014] In a third aspect, a use of the corrosion-resistant high-strength cover glass described in the first aspect of the present invention in extreme environments.
[0015] The beneficial effects of the present invention are:
[0016] 1. The corrosion-resistant high-strength cover glass provided by the present invention has a bending strength greater than 160 MPa, a maximum optical transmittance of a 20 mm glass sample greater than 91.2%, and a transmittance of a 1 mm glass sample after reduction less than 1.6%.
[0017] 2. The corrosion-resistant high-strength cover glass provided by the present invention has acid resistance stability and moisture resistance stability of level 1, good mechanical properties and processing properties, and can be applied as the main material of glass cover plates for extreme environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0019] Figure 1 It is a comparative curve diagram of transmittance of glass materials with a thickness of 1 mm and 20 mm in Example 1 within a wavelength range of 350 nm to 1000 nm.
[0020] Figure 2 It is a comparison chart of the bending strength of glass materials of Examples 1 to 10 and Comparative Examples 1 to 5. DETAILED DESCRIPTION
[0021] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0022] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0023] Considering that the optical properties, chemical stability and mechanical properties of existing cover glass cannot adapt to the harsh extreme environment such as Antarctica, the present invention proposes corrosion-resistant high-strength cover glass and its preparation method and its application in extreme environments.
[0024] A typical embodiment of the present invention provides a corrosion-resistant high-strength cover glass, which is composed of the following components in parts by weight:
[0025] SiO2 48.0-60.0 parts by weight, Al2O3 19.0-25.0 parts by weight, B2O3 3.0-7.0 parts by weight, K2O0-2.0 parts by weight, Na2O 13.0-17.0 parts by weight, CaO 0-1.0 parts by weight, MgO 0.5-4.0 parts by weight, CeO2 0.5-2.0 parts by weight, Bi2O3 0-3.0 parts by weight, Sb2O3 0-3.0 parts by weight, SnO2 0.1-2.0 parts by weight, Li2O 0.1-2.0 parts by weight, the total weight of each component is 100 parts by weight;
[0026] Among them, K2O and CaO cannot be 0 at the same time, and Bi2O3 and Sb2O3 cannot be 0 at the same time.
[0027] In the present invention, SiO2 is a glass-forming oxide. As the main constituent of glass, it provides the basic framework of the structure and gives the glass good chemical stability and mechanical strength. The appropriate SiO2 content can reduce the thermal expansion coefficient of the glass and improve the thermal stability, chemical stability, softening temperature, heat resistance, hardness and mechanical strength of the glass. Too high a content of SiO2 may lead to an increase in the melting point and difficulty in processing; too low a content of SiO2 may weaken the chemical stability and mechanical strength of the glass. SiO2 can be 49.0 to 60.0 parts by weight, 48.0 to 56.0 parts by weight, 48.0 to 53.0 parts by weight, 50.0 to 60.0 parts by weight, 48.0 to 50.0 parts by weight, 49.0 to 51.0 parts by weight, 50.0 to 52.0 parts by weight, 51.0 to 53.0 parts by weight, 52.0 to 54.0 parts by weight, 53.0 to 55.0 parts by weight, 56.0 to 60.0 parts by weight, etc.
[0028] Al2O3 is an essential component for improving the chemical stability of glass, which can reduce the tendency of glass crystallization. It is also a component for improving the hardness and mechanical strength of glass and increasing the tensile elastic modulus. In the glass network structure, alumina is a network intermediate oxide, between the network generator and the network exogenous body. Al2O3 can be 19.2 to 25.0 parts by weight, 19.0 to 22.0 parts by weight, 19.2 to 22.0 parts by weight, 19.0 to 21.0 parts by weight, 19.2 to 21.0 parts by weight, 19.2 to 20.0 parts by weight, 19.5 to 21.0 parts by weight, 20.0 to 25.0 parts by weight, 22.0 to 25.0 parts by weight, etc.
[0029] In the present invention, B2O3 is also a glass-forming oxide, which has boron oxide triangles [BO3] and boron oxide tetrahedrons [BO4] as structural units, and together with silicate tetrahedrons in borosilicate glass, forms a structural network. B2O3 can reduce the viscosity of glass at high temperatures and increase the viscosity of glass at low temperatures, so the glass with a higher B2O3 content has a wider forming temperature range. B2O3 also plays a role in fluxing, accelerating the dissolution and clarification of glass. However, when the amount of B2O3 added is too high, due to the increase in boron oxide triangles, the expansion coefficient of the glass increases, boron anomaly occurs, and the chemical stability of the glass is reduced. B2O3 can be 3.0 to 5.7 parts by weight, 3.0 to 5.0 parts by weight, 3.0 to 4.5 parts by weight, 3.0 to 4.0 parts by weight, 4.0 to 5.0 parts by weight, 3.0 to 3.5 parts by weight, 3.5 to 4.0 parts by weight, etc.
[0030] In the present invention, K2O and Na2O are the network oxides of the glass. Alkali metal ions are easy to move and diffuse in the glass, which can reduce the viscosity of the glass during high-temperature melting and make the glass easy to melt. They are good fluxing agents, but the amount of introduction should not be too much. Excessive introduction will increase the thermal expansion coefficient of the glass and reduce the chemical stability, thermal stability and mechanical strength of the glass. In addition, Na2O in the glass + Chemical strengthening is also called ion exchange strengthening. Its principle is to place the glass in molten salt (such as potassium nitrate) at a certain temperature to make the small radius ions (such as Na + ) and large radius ions in molten salts (such as K + ) is replaced, thereby producing a "squeezing" effect on the glass surface, forming a surface compressive stress layer, and improving the mechanical strength of the glass material. K2O can be 0-1.5 weight parts, 0-1.4 weight parts, 0-1.3 weight parts, 0-1.2 weight parts, 0-0.9 weight parts, 0-0.5 weight parts, 0-0.1 weight parts, 0.1-1.5 weight parts, 0.5-1.5 weight parts, 0.5-1.4 weight parts, 0.5-1.3 weight parts, 0.5-1.2 weight parts, etc. Na2O can be 13.0-16.0 weight parts, 13.0-15.0 weight parts, 13.0-14.0 weight parts, 13.0-13.5 weight parts, 13.5-15.0 weight parts, 13.5-14.0 weight parts, etc.
[0031] In the present invention, the introduction of CaO can increase the chemical stability and mechanical strength of the glass, but when the amount introduced is large, the glass is easily crystallized and the thermal stability of the glass is reduced. At the same time, CaO can reduce the viscosity of the glass at high temperature, which is conducive to clarification; the introduction of MgO can improve the thermal stability of the glass, and the introduction of MgO will reduce the thermal expansion coefficient of the glass, but too much MgO will increase the viscosity of the glass, resulting in difficulty in glass molding. MgO and CaO jointly enhance the mechanical strength and chemical durability of the glass in the present invention, and the addition of MgO is particularly helpful to reduce the increase in the thermal expansion coefficient caused by CaO. CaO can be 0.1 to 1.0 parts by weight, 0.1 to 0.8 parts by weight, 0.1 to 0.6 parts by weight, 0.1 to 0.5 parts by weight, 0.1 to 0.4 parts by weight, 0.2 to 0.6 parts by weight, 0.2 to 0.5 parts by weight, 0.2 to 0.4 parts by weight, 0.3 to 0.6 parts by weight, 0.3 to 0.5 parts by weight, 0.3 to 0.4 parts by weight, 0.4 to 0.6 parts by weight, etc. MgO may be 0.5-4.0 parts by weight, 0.6-4.0 parts by weight, 0.8-4.0 parts by weight, 1.0-4.0 parts by weight, 1.5-3.5 parts by weight, 1.7-3.5 parts by weight, 2.3-3.5 parts by weight, 2.5-3.5 parts by weight, 1.7-2.3 parts by weight, etc.
[0032] In the present invention, CeO2 is a variable valence oxide, CeO2 decomposes oxygen at high temperature, and the more oxygen can be separated from its chemical bond for every 1°C increase in temperature, the greater the clarification effect. The solubility of oxygen decreases with increasing temperature, thereby producing a clarification effect. At the same time, CeO2 has excellent thermal stability and physical properties, which can improve the impact resistance and heat resistance of glass, making the glass harder and more durable. At the same time, CeO2 can be used as a radiation stabilizer to improve the radiation resistance of glass. CeO2 can be 0.5 to 2.0 parts by weight, 0.8 to 2.0 parts by weight, 0.8 to 1.7 parts by weight, 0.8 to 1.6 parts by weight, 0.8 to 1.3 parts by weight, 0.8 to 1.2 parts by weight, 1.0 to 1.7 parts by weight, 1.2 to 1.7 parts by weight, 1.3 to 1.7 parts by weight, 1.4 to 1.7 parts by weight, etc.
[0033] In the present invention, the addition of Bi2O3 can improve the refractive index and dispersion ability. Bi2O3 also helps to improve the thermal stability of glass and enhance its light absorption ability. At the same time, since the Bi element (usually introduced as Bi2O3 or Bi(NO3)3) can be reduced to black under a high-temperature hydrogen atmosphere, this property can be used to optimize the stray light absorption effect. However, the introduction of Bi2O3 requires precise control. Excessive addition of Bi2O3 may lead to a significant reduction in the chemical stability of the glass, especially when reacting with reducing gases, its stability problem is more prominent. In addition, high concentrations of Bi2O3 may cause serious erosion to the melting container during the glass melting process, which limits its scope of application in glass production. In addition, too much Bi2O3 may also promote crystallization of glass, affecting its transparency and optical uniformity. On the contrary, insufficient Bi2O3 content makes it difficult to improve optical properties. The introduction of SnO2 can enhance the transparency and heat resistance of glass. Meanwhile, in the process of glass melting, SnO2 will react with other glass components to form hard crystals. These crystals are dispersed in the glass, which can increase the hardness and flexural strength of the glass and reduce the possibility of scratches on the glass surface. Sb2O3 can be used as an additive for glass liquid to improve the heat resistance, impact resistance, transparency and other properties of the glass. It can also reduce the thermal expansion coefficient of the glass, making the products of the glass liquid more tough and transparent. SnO2 and Sb2O3 can be used as clarifiers to reduce the difficulty of glass clarification. The present invention improves the stray light absorption rate after glass reduction blackening through the synergistic effect of two or three of the three oxidizing compounds of Bi2O3, SnO2 and Sb2O3. Bi2O3 can be 0.1 to 3.0 parts by weight, 0.1 to 2.5 parts by weight, 0.1 to 2.0 parts by weight, 0.1 to 1.5 parts by weight, 0.1 to 1.2 parts by weight, 0.1 to 1.0 parts by weight, 0.1 to 0.7 parts by weight, 0.1 to 0.5 parts by weight, 0.2 to 3.0 parts by weight, 0.2 to 2.5 parts by weight, 0.2 to 2.0 parts by weight, 0.2 to 1.5 parts by weight, 0.2 to 1.2 Parts by weight, 0.2-1.0 parts by weight, 0.2-0.7 parts by weight, 0.2-0.5 parts by weight, 0.5-1.0 parts by weight, 0.5-1.5 parts by weight, 0.5-2.0 parts by weight, 0.5-2.5 parts by weight, 0.7-2.5 parts by weight, 1.0-2.5 parts by weight, 1.2-2.5 parts by weight, 1.3-2.5 parts by weight, 1.5-2.5 parts by weight, 2.0-2.5 parts by weight, etc. SnO2 can be 0.1-1.5 parts by weight, 0.1-1.3 parts by weight, 0.1-1.0 parts by weight, 0.1-0.8 parts by weight, 0.1-0.4 parts by weight, 0.2-0.8 parts by weight, 0.2-0.4 parts by weight, 0.4-0.8 parts by weight, etc.Sb2O3 can be 0.1-3.0 parts by weight, 0.2-3.0 parts by weight, 0.5-3.0 parts by weight, 1.1-3.0 parts by weight, 1.4-3.0 parts by weight, 1.6-3.0 parts by weight, 2.0-3.0 parts by weight, 2.5-3.0 parts by weight, 0.1-2.5 parts by weight, 0.2-2.5 parts by weight, 0.1-2.0 parts by weight, 0.2-2.0 parts by weight, 0.1-1.6 parts by weight, 0.2-1.6 parts by weight, 0.1-1.4 parts by weight, 0.2-1.4 parts by weight, 0.1-1.0 parts by weight, 0.2-1.0 parts by weight, 0.1-0.5 parts by weight, 0.2-0.5 parts by weight, 0.5-1.5 parts by weight, etc.
[0034] In the present invention, Li2O can combine with oxygen atoms in the glass network to form Li-O bonds, which helps to enhance the network structure of the glass and improve the physical properties of the glass. Moreover, the introduction of Li2O in the present invention can reduce the tendency of crystal formation during the cooling and solidification of the glass, help maintain the amorphous state of the glass, and improve the optical transparency of the glass, thereby making the glass more transparent, improving the optical transmittance of the glass, and reducing the haze of the glass. However, it should be noted that the amount of Li2O used needs to be precisely controlled, and excessive Li2O will reduce the chemical stability of the glass and may cause the glass to be more susceptible to crystallization and phase separation. Li2O can be 0.1 to 1.5 parts by weight, 0.1 to 1.4 parts by weight, 0.1 to 1.0 parts by weight, 0.1 to 0.9 parts by weight, 0.1 to 0.5 parts by weight, 0.5 to 1.5 parts by weight, 0.9 to 1.5 parts by weight, 0.5 to 1.4 parts by weight, 0.9 to 1.4 parts by weight, etc.
[0035] In some embodiments, the weight fraction of Na2O is greater than two thirteen times the weight fraction of K2O.
[0036] In some embodiments, the weight fraction of B2O3 is less than seven-nineteenths of the weight fraction of Al2O3.
[0037] In some embodiments, the sum of the weight parts of CeO2, SnO2, and Sb2O3 is greater than 0.6 weight parts.
[0038] In some embodiments, the bending strength is not less than 160 MPa, preferably 160-173 MPa; the maximum optical transmittance of a 20 mm glass sample is not less than 91.2%, preferably 91.2-92.6%; the transmittance of a 1 mm glass sample after reduction is not higher than 1.6%, preferably 1.2-1.6%.
[0039] Another embodiment of the present invention provides a method for preparing the above-mentioned corrosion-resistant high-strength cover glass, comprising the following steps:
[0040] Mixing the components of the glass material uniformly according to a certain proportion to obtain a mixture;
[0041] The mixture is melted at 1480-1580°C, stirred, clarified, and molded at 1350-1400°C.
[0042] In some embodiments, during stirring, the rotation speed is 15 to 30 r / min, and the stirring time is 3 to 12 hours. There are certain requirements for the uniformity of the liquid before glass forming, so it is necessary to stir the glass liquid before forming at a certain rotation speed for a period of time to improve the uniformity of the liquid. When the uniformity of the liquid is low, the liquid is prone to stratification or agglomeration, making it difficult to melt and homogenize the glass, and even causing streaks or stone defects in severe cases.
[0043] In some embodiments, the melting time is 8 to 30 hours, which is helpful for clarifying the glass liquid.
[0044] In some embodiments, the molding time is 5 to 25 minutes. Rapid molding of glass can prevent the generation of secondary bubbles and impurities.
[0045] In some embodiments, a blackening reduction treatment is also included. Specifically, the blackening reduction treatment lasts for 6000 to 16000 minutes, the pressure is 0.01 to 0.5 MPa, and the temperature is 500 to 650°C. Before the blackening reduction treatment, the formed glass blank is processed into glass rods and / or glass columns by external cylindrical grinding and polishing and internal precision drilling. Specifically, the formed glass is annealed and then subjected to a blackening reduction treatment. Annealing is performed to eliminate stress within the glass to meet the requirements of later cold processing. Specifically, the annealing temperature is 500 to 550°C.
[0046] In one or more embodiments, the glass blank after blackening reduction treatment and the glass blank without blackening reduction treatment are assembled and melt-pressed. Specifically, the glass rod is inserted into the hole of the glass column and then melt-pressed. Specifically, the melting and pressing temperature is 600-650°C and the pressure is (1-10)×10 5 N.
[0047] In one or more embodiments, the glass blank after melting and pressing is chemically strengthened. Specifically, the glass blank after high-temperature melting and pressing is mechanically processed and then chemically strengthened. Specifically, the temperature of the chemical strengthening is 380 to 460° C. and the time is 30 to 600 minutes. Specifically, the molten salt for chemical strengthening is potassium nitrate or a mixture of potassium nitrate and sodium nitrate.
[0048] A third embodiment of the present invention provides an application of the above-mentioned corrosion-resistant high-strength cover glass in extreme environments.
[0049] In some embodiments, the corrosion-resistant high-strength cover glass is used to prepare a glass cover for an optical camera.
[0050] In some embodiments, the extreme environment is the Earth's Antarctic environment.
[0051] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.
[0052] The performance parameters in the following embodiments are measured according to the following methods:
[0053] The thermal expansion coefficient α of the glass sample was tested using the DIL 402 expansion coefficient tester produced by NETZSCH, Germany. Sample preparation: The glass sample was polished into a cylindrical glass strip of Φ6×50mm, and the two end surfaces were parallel. The heating rate was set to 5℃ / min, and the data acquisition cycle was 20ms. Refer to GB / T7962.16~2010.
[0054] The softening point temperature of the glass sample is tested using the Model PPV-1000 / 1200 plate viscometer produced by Orton. Sample preparation: The glass sample is polished into a cylindrical glass strip of Φ6×6mm, and the two end faces are parallel. The sample is placed between the top and bottom discs, which are made of heat-resistant metal alloys with a diameter of 44mm and a thickness of 6mm. The top metal disc is connected to the bottom of the probe rod. Two very thin platinum films (40mm in diameter and 0.001 inches thick) are placed between the sample and the top and bottom discs to facilitate sampling and sample placement. Refer to ASTM C-1351M.
[0055] The transmittance test was carried out using a UV-visible-infrared spectrophotometer.
[0056] After the surface of the polished glass sample is corroded by the test medium with acidity of pH2.9, pH4.6, and pH6.0, observe the time when the purple-blue interference color appears on the glass surface, or the surface becomes mottled or falls off under an incandescent lamp. The acid resistance stability of colorless optical glass is classified in descending order according to the length of time. Refer to GB / T 7962.14~2010.
[0057] Polished glass samples are kept at a constant temperature and humidity of 50°C and 85% relative humidity for 20 hours, and the moisture resistance stability of colorless optical glass is classified in descending order by comparing the turbidity values with those of standard samples H (BaK7) and H (ZK9). Refer to GB / T7962.15~2010.
[0058] The haze of glass samples was tested using the Qunlong CS series haze tester. Sample preparation: The glass samples were ground and polished into Φ32×20mm circular glass sheets. The spectral response was the CIE spectral function Y / V(λ), with a wavelength range of 400-700nm, a wavelength interval of 10nm, and a resolution of 0.01 units. Refer to GB / T24010.
[0059] The bending strength of glass samples is tested using the three-point bending method. The glass sample is processed into the required size for the test, and then the glass sample is placed between two supporting points and a fixed load is applied perpendicular to the center of the sample. Then, by applying different bending moments, the bending stress and strain of the glass are measured under different conditions. Finally, the bending strength of the glass is determined. Refer to GB / T 37781-2019.
[0060] The present invention will be further described below in conjunction with the embodiments.
[0061] Example 1
[0062] The components of the corrosion-resistant high-strength cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1 and Table 3.
[0063] The preparation method of corrosion-resistant high-strength cover glass is as follows: quartz sand, aluminum hydroxide, boric acid, potassium nitrate, sodium nitrate, calcium carbonate, basic magnesium carbonate, cerium dioxide, bismuth oxide, antimony oxide, and lithium carbonate are used as raw materials, and after being fully mixed, they are melted at 1480°C for 8 hours, mechanically stirred (15r / min, 3 hours), assisted with high-temperature clarification, and leak-formed at 1350°C (forming time is 5 minutes) to obtain glass blanks. The glass blanks are placed in an annealing furnace heated to 520°C in advance and annealed for 3 hours. After the insulation is completed, the power is turned off and the temperature is lowered with the furnace to eliminate the stress in the glass to meet the requirements of later cold processing.
[0064] After annealing, the glass blank is processed into glass rods and glass columns of a certain size by grinding and polishing the outer circle and drilling the inner hole precisely. Then, the glass rods and glass columns are placed in a blackening reduction furnace. The blackening reduction program is set. The blackening reduction temperature is 620°C, the reducing gas hydrogen pressure is 0.2MPa, and the blackening reduction time is 10000min. After the blackening reduction treatment is completed, a stray light absorption layer is formed on the surface of the glass. The blackened reduced glass rods are inserted into the holes of the glass columns that have not been blackened and reduced for melting and pressing. The melting and pressing temperature is 620°C and the pressure is 2.5×10 5 N, and then the molten glass blank is machined. Then it is rounded, sliced, chamfered, and polished. The polished glass slice is chemically strengthened at 380°C for 500 minutes, and the molten salt ratio is 85wt% KNO3+15wt% NaNO3. After strengthening, a high-strength glass cover material is obtained.
[0065] Example 2
[0066] The components of the corrosion-resistant high-strength cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1 and Table 3.
[0067] In the preparation method of corrosion-resistant high-strength cover glass, the melting temperature is 1580°C, the melting time is 16h, mechanical stirring (30r / min, 12h), and 1400°C leak molding (molding time is 15min) is performed to obtain a glass blank. The glass blank is placed in an annealing furnace preheated to 520°C for annealing for 3h, and after the insulation is completed, the power is turned off and the temperature is lowered along with the furnace.
[0068] After annealing, the glass blank is processed into glass rods and glass columns of a certain size by grinding and polishing the outer circle and drilling the inner hole precisely. Then, the glass rods and glass columns are placed in a blackening reduction furnace. The blackening reduction program is set. The blackening reduction temperature is 620°C, the reducing gas hydrogen pressure is 0.01MPa, and the blackening reduction time is 16000min. After the blackening reduction treatment is completed, a stray light absorption layer is formed on the surface of the glass. The blackened and reduced glass rods are inserted into the holes of the glass columns that have not been blackened and reduced for melting and pressing. The melting and pressing temperature is 620°C and the pressure is 2.5×10 5 N, and then the molten glass blank is machined. Then it is rounded, sliced, chamfered, and polished. The polished glass slice is chemically strengthened at 460°C for 30 minutes, and the molten salt ratio is 85wt% KNO3+15wt% NaNO3. After strengthening, a high-strength glass cover material is obtained.
[0069] Example 3
[0070] The components of the corrosion-resistant high-strength cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1 and Table 3.
[0071] In the preparation method of the corrosion-resistant high-strength cover glass in this embodiment, the melting temperature is 1580°C, the melting time is 30h, mechanical stirring (25r / min, 12h), and pressing and molding at 1400°C (molding time is 25min) to obtain a glass blank. The glass blank is placed in an annealing furnace heated to 520°C in advance and annealed for 3h. After the insulation is completed, the power is turned off and the temperature is lowered along with the furnace.
[0072] After annealing, the glass blank is processed into glass rods and glass columns of certain sizes by grinding and polishing the outer circle and drilling the inner holes precisely. Then, the glass rods and glass columns are placed in a blackening reduction furnace. The blackening reduction program is set to a blackening reduction temperature of 500°C, a reducing gas hydrogen pressure of 0.5 MPa, and a blackening reduction time of 6000 min. After the blackening treatment is completed, a stray light absorption layer is formed on the surface of the glass. The blackened and reduced glass rods are inserted into the holes of the glass columns that have not been blackened and reduced for melting and pressing. The melting and pressing temperature is 620°C and the pressure is 2.5×10 5 N, and then the molten glass blank is machined. Then it is rounded, sliced, chamfered, and polished. The polished glass slice is chemically strengthened at 380°C for 550 minutes, and the molten salt ratio is 85wt% KNO3+15wt% NaNO3. After strengthening, a high-strength glass cover material is obtained.
[0073] Example 4
[0074] The components of the corrosion-resistant high-strength cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1 and Table 3.
[0075] In the preparation method of the corrosion-resistant high-strength cover glass in this embodiment, the melting temperature is 1560°C, the melting time is 20 hours, mechanical stirring (20r / min, 14 hours), and pressing and molding at 1400°C (molding time is 25 minutes) to obtain a glass blank. The glass blank is placed in an annealing furnace heated to 520°C in advance and annealed for 3 hours. After the insulation is completed, the power is turned off and the temperature is lowered along with the furnace.
[0076] After annealing, the glass blank is processed into glass rods and glass columns of certain sizes by grinding and polishing the outer circle and drilling the inner holes precisely. Then, the glass rods and glass columns are placed in a blackening reduction furnace. The blackening reduction program is set. The blackening reduction temperature is 650°C, the reducing gas hydrogen pressure is 0.3MPa, and the blackening reduction time is 9000min. After the blackening reduction treatment is completed, a stray light absorption layer is formed on the surface of the glass. The blackened reduced glass rods are inserted into the holes of the glass columns that have not been blackened and reduced for melting and pressing. The melting and pressing temperature is 620°C and the pressure is 2.5×10 5 N, and then the molten glass blank is machined. Then it is rounded, sliced, chamfered, and polished. The polished glass slice is chemically strengthened at 400°C for 600 minutes, and the molten salt ratio is 85wt% KNO3+15wt% NaNO3. After strengthening, a high-strength glass cover material is obtained.
[0077] Example 5
[0078] The components of the corrosion-resistant high-strength cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1 and Table 3.
[0079] In the preparation method of the corrosion-resistant high-strength cover glass in this embodiment, the melting temperature is 1520°C, the melting time is 25h, mechanical stirring (20r / min, 14h), and the glass blank is formed at 1380°C (forming time is 25min). The glass blank is placed in an annealing furnace heated to 520°C in advance and annealed for 3h. After the insulation is completed, the power is turned off and the temperature is lowered along with the furnace.
[0080] After annealing, the glass blank is processed into glass rods and glass columns of a certain size by grinding and polishing the outer circle and drilling the inner hole precisely. Then, the glass rods and glass columns are placed in a blackening reduction furnace. The blackening reduction program is set. The blackening reduction temperature is 630°C, the reducing gas hydrogen pressure is 0.2MPa, and the blackening reduction time is 12000min. After the blackening reduction treatment is completed, a stray light absorption layer is formed on the surface of the glass. The blackened and reduced glass rods are inserted into the holes of the glass columns that have not been blackened and reduced for melting and pressing. The melting and pressing temperature is 620°C and the pressure is 2.5×10 5 N, and then the molten glass blank is machined. Then it is rounded, sliced, chamfered, and polished. The polished glass slice is chemically strengthened at 420°C for 300 minutes, and the molten salt ratio is 85wt% KNO3+15wt% NaNO3. After strengthening, a high-strength glass cover material is obtained.
[0081] Example 6
[0082] The components of the corrosion-resistant high-strength cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1 and Table 3.
[0083] In the preparation method of the corrosion-resistant high-strength cover glass in this embodiment, the melting temperature is 1560°C, the melting time is 30 hours, mechanical stirring (25r / min, 12 hours), and pressing and molding at 1400°C (molding time is 25 minutes) to obtain a glass blank. The glass blank is placed in an annealing furnace preheated to 520°C for annealing for 3 hours, and after the insulation is completed, the power is turned off and the temperature is lowered along with the furnace.
[0084] After annealing, the glass blank is processed into glass rods and glass columns of a certain size by grinding and polishing the outer circle and drilling the inner hole precisely. Then, the glass rods and glass columns are placed in a blackening reduction furnace. The blackening reduction program is set. The blackening reduction temperature is 620°C, the reducing gas hydrogen pressure is 0.1MPa, and the blackening reduction time is 13000min. After the blackening reduction treatment is completed, a stray light absorption layer is formed on the surface of the glass. The blackened and reduced glass rods are inserted into the holes of the glass columns that have not been blackened and reduced for melting and pressing. The melting and pressing temperature is 620°C and the pressure is 2.5×10 5N, and then the molten glass blank is machined. Then it is rounded, sliced, chamfered, and polished. The polished glass slice is chemically strengthened at 410℃ for 360min, and the molten salt ratio is 85wt% KNO3+15wt% NaNO3. After strengthening, a high-strength glass cover material is obtained.
[0085] Example 7
[0086] The components of the corrosion-resistant high-strength cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1 and Table 3.
[0087] In the preparation method of the corrosion-resistant high-strength cover glass in this embodiment, the melting temperature is 1560°C, the melting time is 30 hours, mechanical stirring (20r / min, 14 hours), and 1400°C leak molding (molding time is 25 minutes) is performed to obtain a glass blank. The glass blank is placed in an annealing furnace heated to 520°C in advance and annealed for 3 hours. After the insulation is completed, the power is turned off and the temperature is lowered along with the furnace.
[0088] After annealing, the glass blank is processed into glass rods and glass columns of a certain size by grinding and polishing the outer circle and drilling the inner holes precisely. Then, the glass rods and glass columns are placed in a blackening reduction furnace. The blackening reduction program is set. The blackening reduction temperature is 620°C, the reducing gas hydrogen pressure is 0.05MPa, and the blackening reduction time is 15000min. After the blackening reduction treatment is completed, a stray light absorption layer is formed on the surface of the glass. The blackened reduced glass rods are inserted into the holes of the glass columns that have not been blackened and reduced for melting and pressing. The melting and pressing temperature is 620°C and the pressure is 2.5×10 5 N, and then the molten glass blank is machined. Then it is rounded, sliced, chamfered, and polished. The polished glass slice is chemically strengthened at 410℃ for 360min, and the molten salt ratio is 85wt% KNO3+15wt% NaNO3. After strengthening, a high-strength glass cover material is obtained.
[0089] Example 8
[0090] The components of the corrosion-resistant high-strength cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1 and Table 3.
[0091] In the preparation method of the corrosion-resistant high-strength cover glass in this embodiment, the melting temperature is 1570°C, the melting time is 30 hours, mechanical stirring (15r / min, 14 hours), and pressing and molding at 1400°C (molding time is 20 minutes) to obtain a glass blank. The glass blank is placed in an annealing furnace heated to 520°C in advance and annealed for 3 hours. After the insulation is completed, the power is turned off and the temperature is lowered along with the furnace.
[0092] After annealing, the glass blank is processed into glass rods and glass columns of a certain size by grinding and polishing the outer circle and drilling the inner hole precisely. Then, the glass rods and glass columns are placed in a blackening reduction furnace. The blackening reduction program is set. The blackening reduction temperature is 600°C, the reducing gas hydrogen pressure is 0.3MPa, and the blackening reduction time is 16000min. After the blackening reduction treatment is completed, a stray light absorption layer is formed on the surface of the glass. The blackened and reduced glass rods are inserted into the holes of the glass columns that have not been blackened and reduced for melting and pressing. The melting and pressing temperature is 620°C and the pressure is 2.5×10 5 N, and then the molten glass blank is machined. Then it is rounded, sliced, chamfered, and polished. The polished glass slice is chemically strengthened at 390°C for 360 minutes, and the molten salt ratio is 85wt% KNO3+15wt% NaNO3. After strengthening, a high-strength glass cover material is obtained.
[0093] Example 9
[0094] The components of the corrosion-resistant high-strength cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1 and Table 3.
[0095] In the preparation method of the corrosion-resistant high-strength cover glass in this embodiment, the melting temperature is 1560°C, the melting time is 30h, mechanical stirring (30r / min, 14h), and 1400°C leak molding (molding time is 20min) is performed to obtain a glass blank. The glass blank is placed in an annealing furnace preheated to 520°C for annealing for 3h, and after the insulation is completed, the power is turned off and the temperature is lowered along with the furnace.
[0096] After annealing, the glass blank is processed into glass rods and glass columns of a certain size by grinding and polishing the outer circle and drilling the inner hole precisely. Then, the glass rods and glass columns are placed in a blackening reduction furnace. The blackening reduction program is set. The blackening reduction temperature is 600°C, the reducing gas hydrogen pressure is 0.4MPa, and the blackening reduction time is 16000min. After the blackening reduction treatment is completed, a stray light absorption layer is formed on the surface of the glass. The blackened and reduced glass rods are inserted into the holes of the glass columns that have not been blackened and reduced for melting and pressing. The melting and pressing temperature is 620°C and the pressure is 2.5×10 5 N, and then the molten glass blank is machined. Then it is rounded, sliced, chamfered, and polished. The polished glass slice is chemically strengthened at 400℃ for 360min, and the molten salt ratio is 85wt% KNO3+15wt% NaNO3. After strengthening, a high-strength glass cover material is obtained.
[0097] Example 10
[0098] The components of the corrosion-resistant high-strength cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1 and Table 3.
[0099] In the preparation method of the corrosion-resistant high-strength cover glass in this embodiment, the melting temperature is 1550°C, the melting time is 30 hours, mechanical stirring (30r / min, 14 hours), and pressing and molding at 1400°C (molding time is 20 minutes) to obtain a glass blank. The glass blank is placed in an annealing furnace heated to 520°C in advance and annealed for 3 hours. After the insulation is completed, the power is turned off and the temperature is lowered along with the furnace.
[0100] After annealing, the glass blank is processed into glass rods and glass columns of a certain size by grinding and polishing the outer circle and drilling the inner hole precisely. Then, the glass rods and glass columns are placed in a blackening reduction furnace. The blackening reduction program is set. The blackening reduction temperature is 620°C, the reducing gas hydrogen pressure is 0.5MPa, and the blackening reduction time is 8000min. After the blackening reduction treatment is completed, a stray light absorption layer is formed on the surface of the glass. The blackened reduced glass rods are inserted into the holes of the glass columns that have not been blackened and reduced for melting and pressing. The melting and pressing temperature is 620°C and the pressure is 2.5×10 5 N, and then the molten glass blank is machined. Then it is rounded, sliced, chamfered, and polished. The polished glass slice is chemically strengthened at 400℃ for 460min, and the molten salt ratio is 85wt% KNO3+15wt% NaNO3. After strengthening, a high-strength glass cover material is obtained.
[0101] Comparative Examples 1 to 5
[0102] The components of the glasses of Comparative Examples 1 to 5, the weight percentage of each component, and the physical properties of the glasses obtained are shown in Tables 2 and 4.
[0103] The preparation steps and parameters of the glass in Comparative Examples 1 to 5 are the same as those in Example 1.
[0104] Table 1 Components and contents of corrosion-resistant high-strength cover glass of Examples 1 to 10 of the present invention
[0105]
[0106] Table 2 Components and contents of cover glass of comparative examples 1 to 5 of the present invention
[0107]
[0108] Table 3 Performance test results of glass samples of Examples 1 to 10
[0109]
[0110]
[0111] Table 4 Performance test results of glass samples of Comparative Examples 1 to 5
[0112]
[0113]
[0114] In Tables 3 and 4, the samples used in the test item "Maximum transmittance of 1mm sample after reduction" are glass samples after blackening treatment, and the samples used in other test items are only glass samples before blackening treatment. Studies have shown that other properties except optical properties do not change before and after reduction.
[0115] Embodiments 1 to 10 have better optical transmittance, haze performance, bending strength and corrosion resistance of the glass by reasonably adding corresponding components and controlling the ratio of each component in the raw materials. As can be seen from Table 3, the optical transmittance of the corrosion-resistant high-strength cover glass obtained in Embodiments 1 to 10 of the present invention is as follows: within the wavelength range of 350 to 1000 nm, the maximum transmittance of the 20 mm glass sample is ≥91.2%, and the maximum transmittance of the 1 mm sample after reduction is ≤1.6%. At the same time, the acid and moisture resistance stability are both level 1, which can maintain the stability of the internal structure of the glass for a long time, and the bending strength is ≥160 MPa. The comprehensive performance is better than the glass involved in Comparative Examples 1 to 5.
[0116] Figure 1 It is a comparative curve diagram of transmittance of glass materials with a thickness of 1 mm and 20 mm in Example 1 within a wavelength range of 350 nm to 1000 nm.
[0117] Figure 2 It is a comparison chart of the bending strength of glass materials of Examples 1 to 10 and Comparative Examples 1 to 5.
[0118] From the above, it can be seen that the corrosion-resistant high-strength cover glass provided by Examples 1 to 10 of the present invention has excellent optical transmittance, low haze, high bending strength, excellent corrosion resistance and good processing performance. This is because Examples 1 to 10 of the present invention adjust the proportion of each component raw material in the preparation of the corrosion-resistant high-strength cover glass and set a suitable stirring speed and time. Therefore, the corrosion-resistant high-strength cover glass of the present invention has high optical transmittance, low haze, high bending strength and excellent corrosion resistance, and has broad application prospects.
[0119] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A corrosion-resistant high-strength cover glass, characterized in that: In parts by weight, it is composed of the following components: SiO2 48.0-60.0 parts by weight, Al2O3 19.0-25.0 parts by weight, B2O3 3.0-7.0 parts by weight, K2O0-2.0 parts by weight, Na2O 13.0-17.0 parts by weight, CaO 0-1.0 parts by weight, MgO 0.5-4.0 parts by weight, CeO2 0.5-2.0 parts by weight, Bi2O3 0-3.0 parts by weight, Sb2O3 0-3.0 parts by weight, SnO2 0.1-2.0 parts by weight, Li2O 0.1-2.0 parts by weight, the total weight of each component is 100 parts by weight; Among them, K2O and CaO cannot be 0 at the same time, and Bi2O3 and Sb2O3 cannot be 0 at the same time.
2. The corrosion-resistant high-strength cover glass according to claim 1, characterized in that: SiO2 is 49.0-60.0 parts by weight, or 48.0-56.0 parts by weight, or 48.0-53.0 parts by weight, or 50.0-60.0 parts by weight, or 48.0-50.0 parts by weight, or 49.0-51.0 parts by weight, or 50.0-52.0 parts by weight, or 51.0-53.0 parts by weight, or 52.0-54.0 parts by weight, or 53.0-55.0 parts by weight, or 56.0-60.0 parts by weight; Or, Al2O3 is 19.2-25.0 parts by weight, or 19.0-22.0 parts by weight, or 19.2-22.0 parts by weight, or 19.0-21.0 parts by weight, or 19.2-21.0 parts by weight, or 19.2-20.0 parts by weight, or 19.5-21.0 parts by weight, or 20.0-25.0 parts by weight, or 22.0-25.0 parts by weight; Or, B2O3 is 3.0-5.7 parts by weight, or 3.0-5.0 parts by weight, or 3.0-4.5 parts by weight, or 3.0-4.0 parts by weight, or 4.0-5.0 parts by weight, or 3.0-3.5 parts by weight, or 3.5-4.0 parts by weight; Or, K2O is 0-1.5 parts by weight, or 0-1.4 parts by weight, or 0-1.3 parts by weight, or 0-1.2 parts by weight, or 0-0.9 parts by weight, or 0-0.5 parts by weight, or 0-0.1 parts by weight, or 0.1-1.5 parts by weight, or 0.5-1.5 parts by weight, or 0.5-1.4 parts by weight, or 0.5-1.3 parts by weight, or 0.5-1.2 parts by weight; Or, Na2O is 13.0-16.0 parts by weight, or 13.0-15.0 parts by weight, or 13.0-14.0 parts by weight, or 13.0-13.5 parts by weight, or 13.5-15.0 parts by weight, or 13.5-14.0 parts by weight; Or, CaO is 0.1-1.0 part by weight, or 0.1-0.8 part by weight, or 0.1-0.6 part by weight, or 0.1-0.5 part by weight, or 0.1-0.4 part by weight, or 0.2-0.6 part by weight, or 0.2-0.5 part by weight, or 0.2-0.4 part by weight, or 0.3-0.6 part by weight, or 0.3-0.5 part by weight, or 0.3-0.4 part by weight, or 0.4-0.6 part by weight; Or, MgO is 0.5-4.0 parts by weight, or 0.6-4.0 parts by weight, or 0.8-4.0 parts by weight, or 1.0-4.0 parts by weight, or 1.5-3.5 parts by weight, or 1.7-3.5 parts by weight, or 2.3-3.5 parts by weight, or 2.5-3.5 parts by weight, or 1.7-2.3 parts by weight; Or, CeO2 is 0.5-2.0 parts by weight, or 0.8-2.0 parts by weight, or 0.8-1.7 parts by weight, or 0.8-1.6 parts by weight, or 0.8-1.3 parts by weight, or 0.8-1.2 parts by weight, or 1.0-1.7 parts by weight, or 1.2-1.7 parts by weight, or 1.3-1.7 parts by weight, or 1.4-1.7 parts by weight; Or, Bi2O3 is 0.1-3.0 parts by weight, or 0.1-2.5 parts by weight, or 0.1-2.0 parts by weight, or 0.1-1.5 parts by weight, or 0.1-1.2 parts by weight, or 0.1-1.0 parts by weight, or 0.1-0.7 parts by weight, or 0.1-0.5 parts by weight, or 0.2-3.0 parts by weight, or 0.2-2.5 parts by weight, or 0.2-2.0 parts by weight, or 0.2-1.5 parts by weight, or 0.2-1.2 parts by weight. parts by weight, or 0.2-1.0 parts by weight, or 0.2-0.7 parts by weight, or 0.2-0.5 parts by weight, or 0.5-1.0 parts by weight, or 0.5-1.5 parts by weight, or 0.5-2.0 parts by weight, or 0.5-2.5 parts by weight, or 0.7-2.5 parts by weight, or 1.0-2.5 parts by weight, or 1.2-2.5 parts by weight, or 1.3-2.5 parts by weight, or 1.5-2.5 parts by weight, or 2.0-2.5 parts by weight; Or, SnO2 is 0.1-1.5 parts by weight, or 0.1-1.3 parts by weight, or 0.1-1.0 parts by weight, or 0.1-0.8 parts by weight, or 0.1-0.4 parts by weight, or 0.2-0.8 parts by weight, or 0.2-0.4 parts by weight, or 0.4-0.8 parts by weight; Or, Sb2O3 is 0.1-3.0 parts by weight, or 0.2-3.0 parts by weight, or 0.5-3.0 parts by weight, or 1.1-3.0 parts by weight, or 1.4-3.0 parts by weight, or 1.6-3.0 parts by weight, or 2.0-3.0 parts by weight, or 2.5-3.0 parts by weight, or 0.1-2.5 parts by weight, or 0.2-2.5 parts by weight, or 0 .1 to 2.0 parts by weight, or 0.2 to 2.0 parts by weight, or 0.1 to 1.6 parts by weight, or 0.2 to 1.6 parts by weight, or 0.1 to 1.4 parts by weight, or 0.2 to 1.4 parts by weight, or 0.1 to 1.0 parts by weight, or 0.2 to 1.0 parts by weight, or 0.1 to 0.5 parts by weight, or 0.2 to 0.5 parts by weight, or 0.5 to 1.5 parts by weight; Or, Li2O is 0.1-1.5 parts by weight, or 0.1-1.4 parts by weight, or 0.1-1.0 parts by weight, or 0.1-0.9 parts by weight, or 0.1-0.5 parts by weight, or 0.5-1.5 parts by weight, or 0.9-1.5 parts by weight, or 0.5-1.4 parts by weight, or 0.9-1.4 parts by weight.
3. The corrosion-resistant high-strength cover glass according to claim 1, characterized in that Na The weight of K2O is greater than two-thirteen times the weight of K2O; or, the weight fraction of B2O3 is less than seven-nineteenths of the weight fraction of Al2O3; Or, the sum of the weight parts of CeO2, SnO2, and Sb2O3 is greater than 0.6 weight parts.
4. The corrosion-resistant high-strength cover glass according to claim 1, characterized in that: The bending strength is not less than 160MPa, preferably 160-173MPa; the maximum optical transmittance of a 20mm glass sample is not less than 91.2%, preferably 91.2-92.6%; the transmittance of a 1mm glass sample after reduction is not higher than 1.6%, preferably 1.2-1.6%.
5. A method for preparing the corrosion-resistant high-strength cover glass according to claim 1, characterized in that: The steps include: Mixing the components of the glass material uniformly in proportion to obtain a mixture; The mixture is melted at 1480-1580°C, stirred, clarified, and molded at 1350-1400°C.
6. The method for preparing the corrosion-resistant high-strength cover glass according to claim 5, characterized in that during stirring, the rotation speed is 15 to 30 r / min and the stirring time is 3 to 12 h; Or, the melting time is 8 to 30 hours; Or, the molding time is 5 to 25 minutes.
7. The method for preparing the corrosion-resistant high-strength cover glass according to claim 5, characterized in that: The stirring process also includes a blackening reduction treatment; preferably, the blackening reduction treatment lasts for 6000 to 16000 minutes, the pressure is 0.01 to 0.5 MPa, and the temperature is 500 to 650°C; preferably, the formed glass is annealed and then subjected to a blackening reduction treatment; preferably, the annealing temperature is 500 to 550°C.
8. The method for preparing the corrosion-resistant high-strength cover glass according to claim 7, characterized in that: During stirring, the blackened reduction treated glass blank and the unblackened reduction treated glass blank are assembled and melt-pressed; preferably, a glass rod is inserted into the hole of the glass column and then melt-pressed. Preferably, the melt-pressing temperature is 600-650° C. and the pressure is (1-10)×10 5 N; Preferably, the glass blank after melting and pressing is chemically strengthened; preferably, the glass blank after high-temperature melting and pressing is mechanically processed and then chemically strengthened; preferably, the temperature of the chemical strengthening is 380-460° C. and the time is 30-600 min.
9. Use of the corrosion-resistant high-strength cover glass according to any one of claims 1 to 4 in extreme environments.
10. The use according to claim 9, characterized in that: The corrosion-resistant high-strength cover glass is used to prepare a glass cover for an optical camera; Alternatively, the extreme environment is the Antarctic environment of the Earth.
Citation Information
Patent Citations
Cover glass and method for producing cover glass
CN102557464A
Strengthened Glass
CN104039726A
Low-viscosity and high-aluminum glass, preparation method and applications thereof
CN111018346A
Anti-blue-light high-strength lithium-aluminum-silicon cover plate glass and preparation method and application thereof
CN113121109A
Float ultra-thin photo-thermal electronic glass and preparation method thereof
CN117447076A